PENGARUH KARAKTERISTIK PEMERINTAH DAERAH, TEMUAN AUDIT (BPK) DAN LEVERAGE TERHADAP KINERJA PEMERINTAH DAERAH (Studi Empiris Pemerintah Daerah Kabupaten/Kota Di Provinsi Riau) - Galang Afrian; R. Adri Satriawan Surya; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The aim of this study was to test the effect of the characteristics of the local government, the audit findings (CPC) and leverage on the performance of local government (Local Government empirical studies regencies / cities in Riau Province). Population in this research is the Regional Government of Regency / City in Riau Province has all the complete data include: Balance to get the Total Assets, Budget Realization Report (LRA) to get the PAD, DAU, DAK, Sharing and total realization of the budget revenues, as well as the need BPK audit examination report in 2009-2013 to get the number of audit findings. Data used in this research is secondary data. Data collection techniques in this research is the study of documentation and literature. The data analysis using descriptive method and multiple regression formula. From the research results showed the influence of regional wealth levels of local government performance is positive and significant. Influence shopping areas, audit findings and leverage of local government performance is positive and significant. Based on the results of research known that all independent variables have a strong relationship with local government performance. Also showed that the level of regional wealth, shopping areas, audit findings and jointly leverage effect on the performance of local governments amounted to 76.90%. For authors suggest that this research is still in need of some repairs to be done in future studies related to the object of study similar to this study in the future, such as by adding a few other variables to analyze the performance of local government.Keywords:Characteristics, Audit, Leverage and Performance.